Influence of Customer Satisfaction and Customer Experience on Repurchase Intention of Express Delivery Services for Export Activities Through United Parcel Service (UPS) in Java and Bali, Indonesia - Andry Gunawan; Hananiel Mennoverdi Gunawan (Universitas Pelita Harapan, 2024)
This study aims to determine the effect of the variables Price fairness (PRF), Customs clearance (CCE), Use of Supporting technology (STC), and Total time in transit (TTT) on Customer experience (CEX) and Customer satisfaction (CSA) which then affect Repurchase intention (RPI) for express delivery services in export activities. The data used are primary data with a valid sample of 140 out of 168 respondents (out of 508 samples) which was taken using purposive sampling because the determination of the sample is carried out with certain considerations, samples taken in full month of September 2024. The finding of this study indicates a significant positive result on the relationship between Customer experience on Repurchase intention and Customer satisfaction on Repurchase intention. Other findings show that United Parcel Service (UPS) is expected to pay attention to price fairness, the process of releasing goods from customs areas/ Customs clearance, the use of supporting technology, and total delivery time that influence the formation of positive Customer experience and Customer satisfaction aimed at increasing the repurchsae intention of express delivery services for export activities.